Process of argument : an introduction - Boylan, Michael (New York : Routledge / Taylor & Francis Group, 2020)
The Process of Argument: An Introduction is a necessary companion for anyone seeking to engage in successful persuasion: To organize, construct, and communicate arguments. It is both comprehensive and accessible: An authoritative guide to logical thinking and effective communication. The book begins with techniques to improve reading comprehension, including guides on navigating through fake news and internet trolls. Then, readers are taught how to reconstruct deductive, inductive, and abductive presentations so that the logical structure is explicit. And finally, there is a step-by-step guide for responding to these texts via the argumentative essay. Along the way are current examples from social media and elsewhere on the internet along with guides for assessing truth claims in an ever-complicated community worldview. Throughout, are carefully selected reading questions and exercises that will pace readers in order to ensure that the text is securely grasped and successfully applied. Key Features Offers guidance on how to read a text through self-analysis and social criticism Provides a step-by-step procedure for allowing the student to move from reading to reconstruction to being prepared to write an effective argumentative essay Presents truth theory and shows readers how they can helpfully acquaint themselves with a version of realistic, foundational epistemology Offers guidelines and helpful tools on how best to structure an argumentative, pro or con, essay Includes expansive coverage of inductive logic through the use and assessment of statistics Covers abductive logic as it applies to the analysis of narrative in argumentative writing Has up-to-date examples from the media, including from blogs, social media, and television Includes a helpful glossary of all important terms in the book
Introduction--Part One: Reading the Text--1. Confronting the Text--2. Critical Reading:Worldviews, Fallacies, and the Common Body of Knowledge--3. Assessing Degrees of Certainty and What it Means--Part Two: Reconstructing the Text--4. Outlining Deductive Logical Argument--5. Outlining Inductive Logical Argument--6. Abductive Logical Outlining--Part Three: Responding to the Text--7. Finding Out What You Believe--8. The Con Essay--9. The Pro Essay--Appendix: The Big Picture--Glossary.
Keywords: English language -- Rhetoric; Persuasion (Rhetoric); Critical thinking; Language and logic; Reasoning; Exposition (Rhetoric); Philosophy